2009
DOI: 10.1007/s10800-009-9971-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cathode impedance on the performances of power-oriented lithium ion batteries

Abstract: Since power batteries have different requirements than traditional energy-oriented lithium ion batteries (LIBs) and their design concept is also different than energy-type cells, some new problems not encountered in energy-oriented LIBs must be carefully considered. This study illustrates that cathode impedance, a contributor to total cell impedance which can be ignored in the traditional energy-type LIBs, plays a very important role in power cells. This study uses 18650 cylindrical power cells consisting of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…These electrodes are typically composed of an active material, a conducting carbon, and a binder. The main resistive components in the composite electrodes are the electronic resistivity ( R el ), the ionic resistivities of the solid ( R ion(s) ) and liquid ( R ion(l) ) phases, and the ion transfer resistivity at the electrode/electrolyte interface ( R int ), as shown in Figure . The resistivity is greatly influenced by the distribution of the components in the electrode and electrolytes (internal factors) as well as the operating conditions such as the charge/discharge rate and temperature (external factors) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These electrodes are typically composed of an active material, a conducting carbon, and a binder. The main resistive components in the composite electrodes are the electronic resistivity ( R el ), the ionic resistivities of the solid ( R ion(s) ) and liquid ( R ion(l) ) phases, and the ion transfer resistivity at the electrode/electrolyte interface ( R int ), as shown in Figure . The resistivity is greatly influenced by the distribution of the components in the electrode and electrolytes (internal factors) as well as the operating conditions such as the charge/discharge rate and temperature (external factors) .…”
Section: Introductionmentioning
confidence: 99%
“…The reaction distribution in composite electrodes has been analyzed previously using modeling simulations. Direct observations of the reaction distribution in composite electrodes with a micrometer-level spatial resolution have been reported only recently. Liu et al observed the inhomogeneous reaction in a LiFePO 4 composite electrode using microbeam X-ray diffraction (XRD) .…”
Section: Introductionmentioning
confidence: 99%
“…In current EV/HEV/PHEV markets, LiMn 2 O 4 is adopted as cathode materials for Li-ion batteries [46]. LiMn 2 O 4 cathode materials provide higher voltage than other materials, but its usage is limited by its short cycle life [15,47,48]. It is observed that the accelerated aging/degradation of LiMn 2 O 4 cathode materials is due to the dissolution of Mn in electrolyte under various charging voltage: with a higher charging voltage than 4.2V or nearly fully discharged.…”
Section: State Of Chargementioning
confidence: 99%
“…18,23 The main reason of migration seems to be convective and capillary forces developed during drying, while diffusion tend to re-homogenize the system. Fast drying and additive migration is typically detrimental for the final electrochemical performance and battery cycle life, [28][29][30] promoting electrode cracking (particularly severe for the case of thick electrodes and water processing), 31,32 poorly interconnected heterogeneous electrode mesostructures 23,24 and poor adhesion to the current collector. 18,29 From a computational perspective, the physical complexity of solvent evaporation in high SC dispersions makes challenging the development of devoted physics-based models.…”
Section: Introductionmentioning
confidence: 99%